Chronic Kidney Disease in the Eastern Region of the State of Mexico: Implication of the Social Determinants of Health - Luis Enrique Hernández Gamundi; Donovan Casas Patiño; Alejandra Rodríguez Torres; Angélica Heredia Sánchez (Revista Finlay)
Background: chronic kidney disease keeps the person who suffers from it immersed in a context of physical, psychological and social dependence that demands unique attention of its kind. Objective: to analyze the social determinants of health present in the care setting for patients with chronic kidney disease. Methods: a qualitative study was carried out in the eastern part of the State of Mexico in which 27 patients with chronic kidney disease participated who answered a semi-structured interview, using the Iramuteq v0.7alpha2 software to code the speeches. Results: the voice of the disease is relegated to be devastating in its attention and way of living; income due to constant travel, medical care costs and unemployment conjugates a deadly trap that conditions the economic fragmentation of the patient; public policies are unattainable -referring to the transplant program-; culture shows a religious symbolism of protection to the health coupled with social stigmatization for suffering chronic kidney disease CKD; the health system transits in lack of service guarantees -dialysis, hemodialysis, lack of supplies-; gender shows equality in care but overload of women in patient care. Conclusions: due to their impact on the way of living and caring for chronic kidney disease, the social determinants of health should be included transdisciplinary in public health policies, where not only epidemiology dictates the approach to renal patients, at this time mathematical models They are not applicable to groups, because social, cultural behaviors and the social determinants of health set the behavior patterns of human beings.